2020
DOI: 10.3389/fcell.2020.00108
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Signaling and Lysosome Positioning Crosstalk Through a Multifunctional Protein, Folliculin

Abstract: FLCN was identified as the gene responsible for Birt-Hogg-Dubé (BHD) syndrome, a hereditary syndrome associated with the appearance of familiar renal oncocytomas. Most mutations affecting FLCN result in the truncation of the protein, and therefore loss of its associated functions, as typical for a tumor suppressor. FLCN encodes the protein folliculin (FLCN), which is involved in numerous biological processes; mutations affecting this protein thus lead to different phenotypes depending on the cellular context. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 151 publications
0
19
0
Order By: Relevance
“…This implies that the concurrence in each patient of variants in two or more genes acting in various steps of the autophagy–lysosomal pathway might explain differences in the clinical expressivity of the GAA mutations. Remarkably, in this study, we identified five LOPD patients (F1-II4, F1-II5, F1-II9, F2-II4 and F2-II5) showing the highest severity index score, deleterious variants affecting important domains of RILP and FNIP2 proteins involved in lysosome cellular positioning and autophagy [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This implies that the concurrence in each patient of variants in two or more genes acting in various steps of the autophagy–lysosomal pathway might explain differences in the clinical expressivity of the GAA mutations. Remarkably, in this study, we identified five LOPD patients (F1-II4, F1-II5, F1-II9, F2-II4 and F2-II5) showing the highest severity index score, deleterious variants affecting important domains of RILP and FNIP2 proteins involved in lysosome cellular positioning and autophagy [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, during nutrient insufficiency, the FLCN–FNIP complex modulates the formation of a FLCN–RILP–Rab complex for promoting the clustering of lysosomes around the nucleus [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We speculate that this is partially because folliculin has so many binding partners, and may select one or more unique partner(s) depending on the differentiation stage and nutrient signaling 46,47 . Furthermore, a long-lasting state of FLCN haploinsu ciency, rather than abrupt null FLCN expression by deletion, may cause different intracellular signaling pathways to keep cellular homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies support a functional role for the FLCN-FNIP complex as a GTPase activating protein involved in the fine modulation of Rag GTPase are nucleotide binding and transmission of the nutrient status to mTORC1 [ 116 ]. It was proposed that the GTPase activating properties of the FLCN-FNIP complex occurs downstream of GATAR1 protein complex and together orchestrate a unique molecular regulation: when amino acid levels are low, the GTPase activating protein activity of GATOR1 promotes the GDP-Rag A7B condition and the FLCN-FNIP complex is recruited at the level of lysosomes to drive the GTPase activating properties toward Rag C/D [ 117 , 118 ].…”
Section: Birt-hogg-dubé (Bhd) Syndromementioning
confidence: 99%